HUBUNGAN ANTARA AKTIVITAS BERMAIN PERAN DENGAN KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA DINI - Rahmaningsih, Ai (STPI Bina Insan Mulia Yogyakarta, 2025)
Social skills are an achievement of maturity in social relationships or interactions. It can also be interpreted as a learning process to adjust to group norms, traditions, and religious morals. This study aims to determine: (1) Early childhood role-playing activities in Group B of RA Nurul Amal, Cinunuk Village, Cileunyi District, Bandung Regency; (2) Early childhood social emotional abilities in Group B of RA Nurul Amal, Cinunuk Village, Cileunyi District, Bandung Regency; and (3) The relationship between role-playing activities and early childhood social emotional abilities in Group B of RA Nurul Amal, Cinunuk Village, Cileunyi District, Bandung Regency. Social emotional abilities are influenced by several factors, one of which is children's activities in role-playing. Children's activities in role play can optimize children's abilities through interacting, recognizing emotions. The research methodology used is through a quantitative approach with a correlation method. This study uses a saturated sampling technique, which means that all populations are sampled. The data collection technique used observation, documentation, and interviews. The results of data analysis show that the relationship between role-playing activities and early childhood social emotional abilities obtained a correlation coefficient price of 0.55. The significance test results obtained t count = 2.774 and t table at a significance level of 5% with db = 18 is 2.101. Because t count = 2.774 > t table = 2.101, Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. In other words, role-playing activities contribute or influence social emotional abilities in Group B RA Nurul Amal Cinunuk Village, Cileunyi District, Bandung Regency by 30.25%. While the remaining 69.75% is influenced by other factors not examined in this study